Amsterdam Groth and Health Longitudinal Study: A 23-Year Follow-Up from Teenager to Adult about Lifestyle and Health - Kemper, H. C. G. (Medicine and Sport Science, 2004)
- Review of AGAHLS and Other Observational Longitudinal Studies on Lifestyle and Health from Adolescence into Adulthood - Longitudinal Data Analysis - Longitudinal Trends, Stability and Error of Biological and Lifestyle Characteristics - Fetal Origins of Musculoskeletal and Cardiovascular Health at Adulthood - Fitness and Fatness in Adolescence and Adulthood as Determinants of Large Artery Properties at Age 36 - Genetic and Environmental Factors in Relation to Adult Lumbar Bone Health - Smoking, Alcohol and Coffee Consumption and Cardiovascular Risk Indicators - Personality, a Determinant of Lifestyle? - Energy Balance in Relation to Body Composition from Adolescence to Adulthood - Is Physical Activity Important for Aerobic Power in Young Males and Females? - Effects of Health Information in Youth on Adult Biological and Lifestyle Risk Factors for Chronic Diseases - Publications from the Amsterdam Growth and Health Longitudinal Study